Enabling full-duplex in multiple access technique for 5G wireless networks over Rician fading channels - Chi-Bao Le; Dinh-Thuan Do (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Nowadays, unmanned aerial vehicle (UAV) relays’assisted Internet of Things (IoT) systems provide facility in order to overcome the large scale fading between source and sink. The full-duplex scheme enables wireless network to provide higher spectrum efficient technology. This paper analyses performance of two users which are served by new emerging non-orthogonal multiple access (NOMA) technique. Exact outage probability of such two users are derived and checked via Monte-Carlo simulation. These analytical results provide guideline to design UAV in real application. This paper provides a comprehensive study to examine impact of interference, fixed power allocation factors to system performance.